Analysis of Students' Expectations, Perceptions, and Hopes regarding Internship Programs for Future Career Opportunities - Aprilita Dina Anggraini; Dinda Putri Nurhaliza (Finance : International Journal of Management Finance, 2024)
This research aims to analyze students' expectations, perceptions and hopes for internship programs in preparing them to face the world of work in the future. Internship programs are often considered as a strategic step in bridging the gap between academic theory and professional practice. This research uses a quantitative approach with a survey method, involving 100 students from various universities in Indonesia who have not yet undertaken an internship program. Data was collected through a questionnaire designed to determine the extent of students' understanding regarding the internship program and what expectations they hope to obtain during the internship. The results of the analysis show that students' expectations of the internship program have a positive and significant influence on their career opportunities, while expectations and perceptions regarding the benefits of the internship program do not show a significant influence. This research provides recommendations to educational institutions and companies to improve the quality of internship programs so that they can have an optimal impact on student work readiness. Thus, an effective internship program can help students develop skills and expand professional networks, which will ultimately increase their career opportunities in the future.